2007
DOI: 10.1289/ehp.9874
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Mono Mac 6, BEAS-2B, and Jurkat Cells to Indoor Dust

Abstract: BackgroundAirway toxicity of indoor dust is not sufficiently understood.ObjectivesOur goal in this study was to describe the effects of indoor dust on human monocyte, epithelial, and lymphocyte cell lines. We aimed to a) obtain a comprehensive and intelligible outline of the transcriptional response; b) correlate differential transcription with cellular protein secretion; c) identify cell line–specific features; and d) search for indoor dust–specific responses.MethodsSettled dust was sampled in 42 German house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…However, we observed no IL-6 and GMCSF release from BEAS2B cells cultured in DMEM with FBS in response to crude HDM ( Figure 6C). Although there have been previous reports that demonstrate the expression of proinflammatory cytokines, including IL-6 and GMCSF in BEAS2B cells in response to direct HDM treatment, they all used recombinant or purified HDMassociated allergens Der p1, Der p2, and Der p9 (10) as inducers and not the crude mix (48). Der p2, for instance, is shown to reconstitute TLR signaling in the absence of MD-2 (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed no IL-6 and GMCSF release from BEAS2B cells cultured in DMEM with FBS in response to crude HDM ( Figure 6C). Although there have been previous reports that demonstrate the expression of proinflammatory cytokines, including IL-6 and GMCSF in BEAS2B cells in response to direct HDM treatment, they all used recombinant or purified HDMassociated allergens Der p1, Der p2, and Der p9 (10) as inducers and not the crude mix (48). Der p2, for instance, is shown to reconstitute TLR signaling in the absence of MD-2 (46).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, similar dominant PAHs such as Nap and Phe were both found in outdoor and indoor dust, possibly due to the higher vapor pressure of Nap and Phe compared to B(b+k)F and subsequently transporting into indoor environment with outdoor air particles. The distribution difference of PAHs between outdoor and indoor dust should depend on the different anthropogenic source of PAHs contamination (Pengchai et al 2005;Riechelmann et al 2007). …”
Section: Pahs Levels In Indoor and Outdoor Dustmentioning
confidence: 99%
“…There are many emitting sources for PAHs in indoor environment including the smoking, cooking, and domestic fuel combustion (He et al 2005;Riechelmann et al 2007). PAHs in outdoor environment can be derived from the vehicle emission, power generation by coal combustion, petroleum refining, and waste burning (Peng et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PAH sources differ between indoor and outdoor dust. Previous studies have suggested that there are additional sources of PAHs in indoor dust, such as domestic heating, smoking, and cooking, in addition to those of outdoor dust, such as heavy motor vehicle traffic release and industrial emissions (Riechelmann et al 2007;Maertens et al 2008;Wang et al 2013). Therefore, it is necessary to evaluate the concentration and identify the source of PAHs in indoor dust to assess the risk to human health.…”
Section: Introductionmentioning
confidence: 99%